Fatigue failure load of two resin-bonded zirconia-reinforced lithium silicate glass-ceramics: Effect of ceramic thickness - Monteiro, Jaiane Bandoli [UNESP] (2018)
Objectives: To evaluate the effect of ceramic thickness on the fatigue failure load of two zirconia-reinforced lithium silicate (ZLS) glass-ceramics, adhesively cemented to a dentin analogue material. Methods: Disc-shaped specimens were allocated into 8 groups (n = 25) considering two study factors: ZLS ceramic type (Vita Suprinity — VS; and Celtra Duo — CD), and ceramic thickness (1.0; 1.5; 2.0; and 2.5 mm). A trilayer assembly (ϕ = 10 mm; thickness = 3.5 mm) was designed to mimic a bonded monolithic restoration. The ceramic discs were etched, silanized and luted (Variolink N) into a dentin analogue material. Fatigue failure load was determined using the Staircase method (100,000 cycles at 20 Hz; initial fatigue load ∼60% of the mean monotonic load-to-failure; step size ∼5% of the initial fatigue load). A stainless-steel piston (ϕ = 40 mm) applied the load into the center of the specimens submerged in water. Fractographic analysis and Finite Element Analysis (FEA) were also performed. Results: The ceramic thickness influenced the fatigue failure load for both ZLS materials: Suprinity (716 N up to 1119 N); Celtra (404 N up to 1126 N). FEA showed that decreasing ceramic thickness led to higher stress concentration on the cementing interface. Significance: Different ZLS glass-ceramic thicknesses influenced the fatigue failure load of the bonded system (i.e. the thicker the glass ceramic is, the higher the fatigue failure load will be). Different microstructures of the ZLS glass-ceramics might affect the fatigue behavior. FEA showed that the thicker the glass ceramic is, the lower the stress concentration at the tensile surface will be.